Dietary patterns are associated with attention-deficit hyperactivity disorder (ADHD) symptoms among preschoolers in South Korea: a prospective cohort study. (4th March 2022) - Lee, Kyung-Shin; Choi, Yoon-Jung; Lim, Youn-Hee; Lee, Ji Young; Shin, Moon-Kyung; Kim, Bung-Nyun; Shin, Choong Ho; Lee, Young Ah; Kim, Johanna Inhyang; Hong, Yun-Chul
ABSTRACT: Objectives: Attention-deficit hyperactivity disorder (ADHD) is a prevalent neurobehavioral disorder in children. There are limited studies for diet or dietary supplement effects on ADHD in preschool children in Asia. This study aimed to determine the association between dietary patterns in 4-year-old children and ADHD symptoms in 6-year-old children. Methods: We estimated dietary intake in 4-year-old children using a food frequency questionnaire. Using 33 food groups, major dietary patterns were identified in relation to the consumption of sweets, vegetables, meats, and carbohydrates. Parents of 6-year-old children used the Korean version of the ADHD Rating Scale for ADHD symptom assessment. Results: A sweet dietary pattern was associated with a higher risk of attention deficit (AD) (relative risk [RR], 1.34; confidence interval [CI], 1.17–1.55), hyperactivity (RR, 1.40; CI, 1.19–1.64), and ADHD symptoms (RR, 1.37; CI, 1.23–1.52). A vegetable dietary pattern was associated with a lower risk of ADHD symptoms (RR, 0.81; CI, 0.72–0.90). Food item analysis of the sweet dietary pattern showed that intake scores for chocolate, chips, and fruit jams positively correlated with AD, hyperactivity, and ADHD symptoms. Discussion: These findings can be useful to further understand the roles of dietary factors in ADHD.